Politics of Quality in Education A Comparative Study of Brazil, China, and Russia - Kauko, Jaakko; Takala, Tuomas; Rinne, Risto (Routledge Research in International and Comparative Education, 2018)
The question of quality has become one of the most important framing factors in education and has been of growing interest to international organisations and national policymakers for decades. Politics of Quality in Education focuses on Brazil, China, and Russia, part of the so-called emerging nations' BRICS block, and draws on a four-year project to develop a new theoretical and methodological approach. The book builds a comparative, sociohistorical, and transnational understanding of political relations in education, with a particular focus on the policies and practices of quality assurance and evaluation (QAE). Tracking QAE processes from international organisations to individual schools, contributors analyse how QAE changes the dynamics in the roles of state, expertise, and governance. The book demonstrates how national and sub-national actors play a central role in the adaptation, modification, or rejection of transnational policies. Politics of Quality in Education will be of great interest to academics, researchers, and postgraduate students engaged in the study of comparative and international education, as well as educational policy and politics. It should also be essential reading for practitioners and policymakers.